Analisis Nilai Etis dan Kesadaran Spiritual dalam Ritual Mendem Panca Dhatu di Desa Adat Delod Tukad - I Gusti Ngurah Agung Panji Tresna; I Gusti Ngurah Sudiana; I Ketut Donder (Jayapangus Press, 2026)
The mendem panca dhatu ritual is a sacred practice of Balinese Hindus performed in the context of constructing and purifying holy sites. This ritual affirms the Balinese cosmological worldview that emphasizes harmony between humans, nature, and the divine through reverence for natural elements as instruments of spiritual purification and symbols of cosmic interconnectedness. However, amid modernization and the shifting values of religiosity, the meaning of this ritual tends to be simplified, potentially neglecting the profound ethical and spiritual dimensions embedded within it. This condition calls for an in-depth study to reveal the substantive meaning of the ritual as an expression of religious consciousness and as a value system that sustains the social, moral, and ecological life of Balinese society sustainably. This study aims to examine the ethical and spiritual values within the mendem panca dhatu ritual in Desa Adat Delod Tukad by employing the concepts of shuddha-bhava (inner purity) and cinmaya-bhava (spiritual awareness) as its main analytical framework. The research applies a qualitative method with an ethnographic approach. Informants were selected purposively, involving traditional leaders, priests, and community ritual practitioners. Data were collected through participatory observation, in-depth interviews, and literature review of lontar manuscripts, religious texts, and previous studies. Data validation was conducted through source triangulation, methodological triangulation, and member checking to ensure the credibility of the findings. The results indicate that the ethical values of the ritual function as moral guidance and social legitimacy that strengthen communal solidarity. Spiritually, the ritual emphasizes human connectedness with the transcendent through disciplined purity, self-control, and collective awareness in maintaining sacred spaces. The synergy of ethics, spirituality, and cultural identity in this ritual underscores its relevance to the preservation of religious traditions, the formation of social morality, and the maintenance of cosmic harmony within Balinese Hindu society.